Changing Diets, Varying Food Consumption Patterns, and Food Security among Recent Zimbabwean Migrants in Windhoek, Namibia - Godfrey Tawodzera (African Human Mobility Review)
In Zimbabwe, decades of economic and political challenges have generated significant out-migration to neighboring countries including Namibia, perceived by many Zimbabweans as being more politically and economically stable than their home country. While numerous studies have documented these movements, few have interrogated the food security of migrants in host countries, where they are likely to face food security challenges. This study thus sought to investigate the changing dietary and food consumption patterns of recent Zimbabwean migrants in Namibia and the impact on household food security. The researcher collected data from 35 Zimbabwean migrant households in Windhoek through in-depth interviews. Study results show that deteriorating economic conditions and food insecurity were the major drivers of migration from Zimbabwe. The pre-migration diet of most migrants was mixed, consisting of both traditional and Westernized foods. The major food security challenges were: non-availability of foods that migrants consumed while still in Zimbabwe; poor quality of some substitute foods; increased food expenses through importing foods from the home country; and shortage of time to prepare some foods. While most migrant households reported improved household food security compared to the pre-migration period, numerous food challenges remained. Many worried that the changing diet and the consequent increase in the consumption of over-processed foods could have negative health outcomes, hence impacting on their food security as well.